2020
DOI: 10.1016/j.solmat.2019.110334
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic thin-film chalcogenide–silicon tandem solar cells enabled by a diffusion barrier

Abstract: Following the recent success of monolithically integrated Perovskite/Si tandem solar cells, great interest has been raised in searching for alternative wide bandgap top-cell materials with prospects of a fully earthabundant, stable and efficient tandem solar cell. Thin film chalcogenides (TFCs) such as the Cu 2 ZnSnS 4 (CZTS) could be suitable top-cell materials. However, TFCs have the disadvantage that generally at least one high temperature step (> 500 • C) is needed during the synthesis, which could contami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 68 publications
(81 reference statements)
4
69
0
Order By: Relevance
“…3 In order to achieve functional CZTS/Si monolithic devices, it has been suggested that strategies for protecting the bottom Si cell need to be developed. [3][4][5] In this work, we approach this problem through a comparative study of CZTS/Si tandem cells fabricated using three different types of TiN-based diffusion barrier layers. For the first and second, we use atomic layer deposition (ALD) to produce 5 and 10 nm TiN barrier layers, and a 10 nm TiOxNy barrier layer.…”
Section: Introductionmentioning
confidence: 99%
“…3 In order to achieve functional CZTS/Si monolithic devices, it has been suggested that strategies for protecting the bottom Si cell need to be developed. [3][4][5] In this work, we approach this problem through a comparative study of CZTS/Si tandem cells fabricated using three different types of TiN-based diffusion barrier layers. For the first and second, we use atomic layer deposition (ALD) to produce 5 and 10 nm TiN barrier layers, and a 10 nm TiOxNy barrier layer.…”
Section: Introductionmentioning
confidence: 99%
“…This motivation sustains intensive research on alternative materials, with aluminum-doped zinc oxide (AZO) being one of the most promising choice due to the high abundance of Zn and Al [2]. For example, cost effective solar cells based on Cu (In,Ga)Se 2 (CIGS) and Cu 2 ZnSnS 4 (CZTS) absorbers have been fabricated with a TCO based on AZO [6,7]. There are several methods used to deposit AZO, including physical vapor deposition (under various operation conditions for magnetron sputtering, such as radio-frequency [8][9][10][11][12][13][14][15][16][17][18][19][20], medium-frequency [8,[21][22][23][24][25][26], DC [8,16,22,[26][27][28][29][30][31][32][33][34][35][36][37], pulsed DC [38], high power impulse [39,40], ion beam assisted [41], chemical vapor deposition [1,5] and other chemical methods such as spin coating and sol gel [2,…”
Section: Introductionmentioning
confidence: 99%
“…where hv refers to the incident photon energy, N A is the Avogadro's number, and d 0 is the molar concentration of the absorbing molecules (in units of M). The TPA cross-section, σ 2 , has a unit of cm 4 /(photon/s) or cm 4 s. It can also be represented by another informal unit, GM, which is defined by the following: 1GM = 10 −50 cm 4 s The calculated data are also listed in Table 4. Clearly, the value of σ 2 decreases with increasing Ta doping concentration, which is consistent with the experimental observation.…”
Section: Nonlinear Optical Analysismentioning
confidence: 99%
“…Chalcogenide thin films have drawn considerable interest in recent years, owing to their novel properties and broad range of applications in high-performance optical and electric fields, such as phase change random-access memory (PRAM), resistance random-access memory (ReRAM), nonlinear optical absorption (NOA) devices, thin-film solar cells, and so on [1][2][3][4]. Among them, group IIIA metal chalcogenide (GIIIAMC) is an important member.…”
Section: Introductionmentioning
confidence: 99%